Integration of Islamic Values in Learning - M. Zainal Arif (Postgraduate Program Magister Pendidikan Agama Islam, 2019)
This research on the Development of the Model of Integration of Islamic Values in Learning is a contribution to the thought given to the leaders of the Iqra Islamic Boarding School 'Barung-Koto Pulai Koto XI Tarusan, West Sumatra Province, and the results were presented in and disseminated at the Iqra Islamic Boarding School curriculum development workshop. The point is that curriculum development that is integrated with Islamic values in all subjects in learning is an absolute thing to do in PP Iqra '. To strengthen Islamic values, it becomes the soul of the entire academic community. The critical issue that is accommodated by the curriculum is educators and educators who do not yet understand about the boarding school problems, and this is what encourages leaders to provide guidance specifically through workshops, specialized training on nursing, with the intention of uniting the vision and mission, so that the boarding school program can succeed well . Another support that is no less important is the availability of facilities and infrastructure as well as the components needed in building Islamic boarding schools.Penelitian tentang Pengembangan Model Pengintegrasian Nilai-Nilai Islam Dalam Pembelajaran ini merupakan sumbangan pemikiran yang diberikan kepada pimpinan Pondok Pesantren Iqra’ Barung-Koto Pulai Koto XI Tarusan Propinsi Sumatera Barat, dan hasilnya disampaikan dalam dan diseminarkan dalam acara workshop pengembangan kurikulum Pondok Pesantren Iqra'. Intinya bahwa penyusunan kurikulum yang terintegrasi dengan nilai-nilai Islam diseluruh mata pelajaran dalam pembelajaran merupakan hal yang mutlak untuk dilakukan di PP Iqra’. Sebagai upaya memperkokoh nilai-nilai Islam menjadi jiwa seluruh sivitas akademika. Persoalan yang penting disampung kurikulum adalah tenaga pendidik dan kependidikan yang belum memahami tentang persoalan Pondok Pesantren, dan hal ini yang mendorong pimpinan melakukan pembinaan secara khusus melalui workshop, pelatihan khusus tentang kepesantrenan, dengan maksud menyatukan visi dan misi, sehingga program pesantren dapat berhasil dengan baik. Pendukung lain yang tidak kalah pentingnya adalah ketersediaan sarana dan prasarana serta komponen yang diperlukan dalam membangun Pondok Pesantren.